2011
DOI: 10.1111/j.1551-2916.2011.04976.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Processing of High‐Performance 0.74Pb(Mg1/3Nb2/3)O3–0.26PbTiO3 Thin Films on La0.6Sr0.4CoO3‐Buffered Si Substrates for Pyroelectric Arrays Applications

Abstract: To prepare high-performance ferroelectric thin films on Si substrates for pyroelectric arrays applications, 0.74Pb(Mg 1/3 Nb 2/3 ) O 3 -0.26PbTiO 3 (PMN-PT) thin films, with composition beyond morphotropic phase boundary, were deposited by radio-frequency magnetron sputtering. Conductive perovskite La 0.6 Sr 0.4 CoO 3 with resistivity of about 20 lΩ cm was used as a buffer layer between PMN-PT and Pt/Ti/SiO 2 /Si substrates to promote perovskite phase formation for the PMN-PT thin films. The PMN-PT thin films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Compared to the ceramic counterpart (P r of ∼27 C/cm 2 and E c of 4 kV/mm) [16], the P r is lower while the coercive field E c is obviously larger. Similar phenomena was generally observed in the traditional lead-based ferroelectric films (such as PZT and PMN-PT) [4,18], which may be correlated with the size, defect pinning effects, non-180 • domain wall clamping, and film stress [19,20]. In addition, close inspection of the P-E loop indicated that there was a slightly offset both in the vertical and horizontal directions.…”
Section: Methodsmentioning
confidence: 53%
“…Compared to the ceramic counterpart (P r of ∼27 C/cm 2 and E c of 4 kV/mm) [16], the P r is lower while the coercive field E c is obviously larger. Similar phenomena was generally observed in the traditional lead-based ferroelectric films (such as PZT and PMN-PT) [4,18], which may be correlated with the size, defect pinning effects, non-180 • domain wall clamping, and film stress [19,20]. In addition, close inspection of the P-E loop indicated that there was a slightly offset both in the vertical and horizontal directions.…”
Section: Methodsmentioning
confidence: 53%
“…The relatively high dielectric loss tanδ may be due to the high resistivity of the oxide electrode as well as defects, free carrier, and dipole relaxation losses. 27 Further optimization of deposition oxygen pressure and annealing conditions will be performed to reduce the dielectric loss tanδ. Figure 4 shows the room temperature ferroelectric hysteresis loops (P-E) of Mn-PIMNT thin films tested at 1 kHz.…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of domain wall motion to the dielectric properties of Mn-PIMNT ferroelectric thin films was strongly affected by the DC bias. 27 When the DC bias field was small, the domain wall motion was enhanced and the dielectric constant increased with the increase in the DC bias field. This lifting effect was maximized when the bias field was equal to the coercive field.…”
Section: Resultsmentioning
confidence: 99%
“…For ceramics, it has been reported that Columbite method was effective to obtain a singlephase perovskite with excellent electrical properties [22]. For thin films, previous reports describe that single-phase perovskite was obtained using appropriate substrates or by introducing seeding layers between substrates and relaxor thin films such as the use of MgO [17] single-crystal substrate or the introduction of BaTiO 3 [21], PZT [10,14], or PbO [7] as seeding layers. The molecular design of the precursor solutions and optimization of the processing parameters including thermal treatment conditions are also extremely important to obtain good thin films using CSD.…”
Section: Introductionmentioning
confidence: 99%
“…To date, deposition methods of various kinds, such as chemical solution deposition (CSD) [6][7][8][9][10][11][12], sputtering [13][14][15], and pulsed laser deposition [16][17][18][19][20][21], have been reported for the preparation of PMNtype thin films. Among these techniques, CSD is extremely useful for the PMN-PT thin films with complex compositions because of the easy composition control of precursor solutions and low-temperature deposition using higher potential energy of the gel, leading to costeffective processing methods of thin film deposition on a Si substrate as an industrial use.…”
Section: Introductionmentioning
confidence: 99%